#TITLE_ALTERNATIVE# - PRASETYA (NIM : 13205107 ); Dosen Pembimbing: Dr.dr. Oerip S. Santoso, M.Sc., HARYADI
Up to these days, aneurysm diagnose method is still being done manually by medical image observation, either it’s in 2D form (angiogram), or in 3D form (CT or MRI images). Thus, a more effective detection method is needed, because the accuration of aneurysm detection still depends on observer’s subjectivity. Cerebral aneurysm is a cerebrovascular disorder in which weakening and thinning of arterial blood vessel causes a localized dilation or ballooning of the artery that mostly happens on the bifurcation, and is considered as one of the most dangerous medical problem. This aneurysm occur primarily near the arteries at the base of the brain, known as the Circle of Willis. If this problem doesn’t get an immediate care, the aneurysm could explode and cause fatal injury. The main purpose of this final project is to design a method of cerebral aneurysm detection and classify vascular geometry with colour indicator using MatLab software. The method concentrates on curvature analysis to identify geometry property that defines aneurysm and normal vascular respectively. The acquired main curvature value K1 and K2 would be formulated based on curvature shape index equation I=(K1+K2)/K1 and play the role as the base of vascular colouring system. This index represents a simple geometry form such as ball, cylindrical, and hyperbolic in a more accurate way compared to Gaussian or Mean curvature. Thus, by giving a different colour for each geometry, the aneurysm form (ball) could be differed from a normal artery form (cylindrical) and vascular bifurcation (hyperbolic). The result of the simulation shows a good vascular characterization. Aneurysm is visualized with red, normal artery with green, and the inner side of curvature and bifurcation with blue. Hopefully with this method, the accuration will increase with less diagnose time, and will help doctors or medical team in identifying and deciding which care method is suitable.